Improving fault analysis workflow: a table-based approach for per unit equivalent circuits in basic power engineering course - Abdul Rahman, Nur Atiqah; Muhd Yusoff, Muhd Firdaus; Bakri, Fatimatul Anis (2025)
Fault analysis is a fundamental subtopic in the Basic Power Engineering course, a core subject within the Diploma in Electrical Engineering (Electronic) curriculum. A critical step in fault analysis involves deriving a per-unit equivalent circuit from a given one-line diagram of a power system network, which typically includes generators, transmission lines, transformers, and motors. Traditional methods for obtaining per-unit values often rely on a top-down calculation approach, which lacks systematic organization and can lead to errors. To address this limitation, this approach introduces a structured table-based method designed to streamline the calculation of per-unit values and the construction of equivalent circuits. This innovative approach guides students to focus on specific zones within the network, promoting clarity and reducing computational errors. Furthermore, the table-based format facilitates easier evaluation for lecturers, as it provides a clear and organized representation of the calculation process. A preliminary evaluation involving eight students demonstrated the effectiveness of the method, with seven students adopting the table-based approach. Among these, four students achieved fully correct solutions, while three made minor errors attributed to carelessness. The findings indicate that the table-based method enhances both student performance and teaching efficiency. These results suggest that the table-based approach enhances both student understanding and teaching efficiency. Future work will focus on refining the method and expanding its application to broader power system analysis topics.